2022
DOI: 10.48550/arxiv.2208.07341
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fair Assortment Planning

Abstract: Many online platforms, ranging from online retail stores to social media platforms, employ algorithms to optimize their offered assortment of items (e.g., products and contents). These algorithms tend to prioritize the platforms' short-term goals by featuring items with the highest popularity. However, this practice can then lead to too little visibility for the rest of the items, making them leave the platform, and in turn hurting the platform's long-term goals. Motivated by that, we introduce and study a fai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…In other words, the assortment that maximizes revenue consists of the l products with the highest revenues (r i + t∈[m] z t • 1 i∈Vt ), where l ∈ [n]. As a result, FairMax(z, F ) (problem (12)) can be solved optimally in polynomial time by examining at most n potential assortments. Thus, the combination of Theorem 1 and the ability to solve FairMax(z, F ) optimally in polynomial time (i.e., ρ = µ = 1) implies that an optimal solution for P.0 exists.…”
Section: Random Assortment Planning With Group Market Share Constraintsmentioning
confidence: 99%
See 4 more Smart Citations
“…In other words, the assortment that maximizes revenue consists of the l products with the highest revenues (r i + t∈[m] z t • 1 i∈Vt ), where l ∈ [n]. As a result, FairMax(z, F ) (problem (12)) can be solved optimally in polynomial time by examining at most n potential assortments. Thus, the combination of Theorem 1 and the ability to solve FairMax(z, F ) optimally in polynomial time (i.e., ρ = µ = 1) implies that an optimal solution for P.0 exists.…”
Section: Random Assortment Planning With Group Market Share Constraintsmentioning
confidence: 99%
“…Remark: A recent work by [12] proposed an ellipsoid-based method for the assortment planning problem that includes pairwise fairness constraints. In page 14 of [12] (the October 28th, 2022 version), they discussed the case where all items have uniform revenues. They showed that for this special case, their separation oracle is to maximize the summation of a non-negative monotone submodular function and a (not necessarily positive) modular function.…”
Section: Definition 3 (Fairmax) Given Functions F and Gmentioning
confidence: 99%
See 3 more Smart Citations